Structural analysis of flexible pipes and umbilical cables: a bimaterial finite element modeling technique and a novel experimental approach using a digital image correlation system. - Santos, Caio César Pereira (2019)
The Finite Element Method is a powerful and widespread tool for the structural analysis of flexible pipes and umbilicals. However, it is unfeasible to represent in detail all layers and components of a flexible pipe or umbilical cable in a Finite Element (FE) model, since the calculation time would be unrealistic. Moreover, consistent numerical analysis requires support from experimental results. In this context, this thesis presents numerical and experimental research options, as well as the development of new strategies for the design of FE models of flexible pipes and umbilicals. Using the commercial FE software ABAQUS, the text highlights the development of innovative techniques to represent helical layers, as well as the concept of a two-dimensional FE analysis, supported by analytical formulation. Complementing the numerical approaches, pioneer experimental techniques herein developed are presented, based on optical instrumentation through a Digital Image Correlation (DIC) system. An unconventional use of the DIC system enables the development of an experimental methodology to study umbilicals under crushing loads.